Folk Knowledge in Southern Siberia in the 1770s: Johan Peter Falck’s Ethnobiological Observations - Ståhlberg, Sabira; Svanberg, Ingvar (Studia Orientalia Electronica, 2021)
The southern Siberian Turkic groups were mostly unknown to outsiders when the Swedish scientist Johan Peter Falck (1732–1774) visited their settlements in the early 1770s. Falck led one of the expeditions dispatched between 1768 and 1774 by the Russian Academy of Sciences to different parts of the Russian Empire. As a botanist, zoologist, ethnographer and linguist, during his journeys he recorded information not only about the environment but also about the peoples he met and their political and social organisation, as well as ethnographic data. Falck’s rich and detailed travelogue was published posthumously and soon forgotten, while the rich data remained unattended for almost two centuries. In recent years, mainly biologists have rediscovered the materials, yet ethnobiological data is also plentiful. Knowledge about the environment is crucial for survival, and the complex relationship between humans and their environment is often reflected in names given to living organisms and places or in perceptions of the surroundings. This article focuses on Siberian Turkic folk knowledge among the Chulym Tatars, Kacha, Soyan, and Teleut, based on the observations by Johan Peter Falck in the 1770s. Ethnobiological and linguistic materials are used in an effort to at least partly reconstruct the cognitive world in which these peoples lived and created their concepts of the environment. The article is a preliminary contribution to the study of historical ethnoecology and ethnobiology.